Improving Financial Literacy Amidst the Rise of Illegal Investment in Sumbawa Regency - Fitriyani, Ika; Sudiyarty, Nining; Karmeli, Elly; Rahman, Rosyidah (Lembaga Dongan Dosen, 2023)
Financial literacy is one solution to filter out the negative impacts of technological developments. Understanding financial literacy education plays an important role in changing a person's financial behavior patterns to make decisions. Low financial literacy makes it easier to mismanage finances. Service activities participated in by KKL students and MSME players as a means to improve their education in financial management, especially investment knowledge management. The aim of this activity is to increase financial literacy amidst the rise of fraudulent investments. Through sharing, discussions and public lectures, it is a means of information to make it easier for students to gain financial experience for the present and future. The role of government, universities and financial practitioners needs to be to provide guidance and outreach to the community so that they do not fall into making illegal investments.